2020
DOI: 10.2337/dc20-1567
|View full text |Cite
|
Sign up to set email alerts
|

Processes Underlying Glycemic Deterioration in Type 2 Diabetes: An IMI DIRECT Study

Abstract: The version presented here may differ from the published version. If citing, you are advised to consult the published version for pagination, volume/issue and date of publication Full titleProcesses underlying glycemic deterioration in type 2 diabetes: An IMI DIRECT study

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In a paper by Zaharia et al 30 data generated by hyperinsulinemic euglycemic clamp and C‐peptide response to intravenous glucose were included in a similar cluster analysis, confirming with more sophisticated techniques the existence of the subgroups described by Ahlqvist et al. 29 The same clusters were observed by Dennis et al, 31 who used the HOMA for investigating insulin secretion and sensitivity, and by Bizzotto et al 32 who used mathematical models applied to mixed meal tests for the assessment of both insulin secretion and sensitivity.…”
Section: Discussionsupporting
confidence: 56%
“…In a paper by Zaharia et al 30 data generated by hyperinsulinemic euglycemic clamp and C‐peptide response to intravenous glucose were included in a similar cluster analysis, confirming with more sophisticated techniques the existence of the subgroups described by Ahlqvist et al. 29 The same clusters were observed by Dennis et al, 31 who used the HOMA for investigating insulin secretion and sensitivity, and by Bizzotto et al 32 who used mathematical models applied to mixed meal tests for the assessment of both insulin secretion and sensitivity.…”
Section: Discussionsupporting
confidence: 56%
“…Due to the fact that changes in blood lipids reflect an immediate/rapid response to a changed environment, the cumulative lipid burden reflects cumulative long-term changes, and our results suggested that the blood lipid levels changed before the occurrence of T2DM. In the study by Bizzotto R et al, 26 they found that the progression rates of TG and HDL were correlated with the progression of HbA1c, which may be due to the accumulation of excessive lipids through visceral fat, thus resulting in insulin resistance or excessive glucose production and subsequently resulting in the deterioration of HbA1c. This suggests that visceral fat may be involved in the progression of diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…Another possible explanation of our results is that reduction in insulin clearance is a robust compensatory mechanism that does not initially fail, unlike beta-cell compensation, whose failure is considered a key event in the development of diabetes. However, after diabetes has developed, increasing clearance would reduce the amount of insulin available to promote cellular glucose uptake, and thereby may be an independent predictor of worsening glycemia over time, as demonstrated in a prospective study of 732 patients with recently diagnosed type 2 diabetes [ 33 ]. This suggests that sequential failure of insulin homeostasis mechanisms contribute to the onset of diabetes (failure of insulin secretion to remain high) and potentially to the progression of diabetes (failure of insulin clearance to remain low).…”
Section: Discussionmentioning
confidence: 99%